Predicting Choice: Distraction and Reappraisal as Strategies for Emotion Regulation - Yih, Jennifer (Tufts Archival Research Center, 2005)
The present study was designed to examine to what extent the valence and arousal dimensions of high and low emotion pictures predict the strategies people choose to regulate their emotions. Using normative ratings as well as physiological measures such as corrugator electromyography (EMG) activity and electrodermal activity (EDA), the results indicate that participant chose distraction in response to high emotion pictures and cognitive reappraisal in response to low emotion pictures. Moreover, the results show that lower normative ratings of valence, higher normative ratings of arousal, and greater EDA predicted a greater likelihood of choosing distraction over reappraisal.